2014
DOI: 10.1007/s10585-014-9657-2
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 expressed on different lung compartments promotes organ specific metastasis by facilitating arrest, extravasation and organ colonization via high affinity ligands on melanoma cells

Abstract: Interactions between molecules on the surface of tumor cells and those on the target organ endothelium play an important role in their arrest in an organ. Galectin-3 on the lung endothelium and high affinity ligands poly-N-acetyllactosamine (polyLacNAc) on N-oligosaccharides on melanoma cells facilitate such interactions. However, to extravasate and colonize an organ the cells must stabilize these interactions by spreading to retract endothelium, degrade exposed basement membrane (BM) and move into parenchyma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…These results, on the levels of production of mRNA and protein, pinpoint Galectin-1 as a potent inducer of extracellular presence of MMPs in osteoarthritic chondrocytes. Similar regulatory events had been reported for Galectin-3 and MMP-1 and MMP-9 in murine B16F10 melanoma cells and for MMP-9 in corneal keratinocytes (42)(43)(44), for MMP-7 upregulation by Galectin-7 in murine and human lymphoma cells, and for coexpression of Galectin-7 and MMP-9 in sections of human laryngeal cancer (45,46). In this context, our finding of enhanced bioavailability of effectors of degeneration prompted us to perform transcriptomic analyses.…”
Section: Discussionsupporting
confidence: 70%
“…These results, on the levels of production of mRNA and protein, pinpoint Galectin-1 as a potent inducer of extracellular presence of MMPs in osteoarthritic chondrocytes. Similar regulatory events had been reported for Galectin-3 and MMP-1 and MMP-9 in murine B16F10 melanoma cells and for MMP-9 in corneal keratinocytes (42)(43)(44), for MMP-7 upregulation by Galectin-7 in murine and human lymphoma cells, and for coexpression of Galectin-7 and MMP-9 in sections of human laryngeal cancer (45,46). In this context, our finding of enhanced bioavailability of effectors of degeneration prompted us to perform transcriptomic analyses.…”
Section: Discussionsupporting
confidence: 70%
“…Gal-3 is expressed on the endothelium of all the major compartments of the normal lung, and the presence of Gal-3 in normal lung tissue is thought to be a homing factor for lung metastasis because it provides a location for cells to adhere as they spread throughout the tissue. 48 For example, endothelium membrane-bound Gal-3 binds high affinity ligands poly-N-acetyllactosamine (polyLacNAc) on N-oligosaccharides on melanoma cells, thus providing adhesion for melanoma cells to metastasize into the lung. Manipulating Gal-3 expression, or expression of Gal-3 substrates in the lung after the onset of a primary tumor elsewhere, could be a means of controlling metastasis to lung.…”
Section: Galectin-3 Contribution To Immunosuppressionmentioning
confidence: 99%
“…In addition, by in vitro assay we noticed lower numbers of attached malignant cells in lung tissue sections of Galectin-3-deficient mice, suggesting that hostderived Galectin-3 plays a pivotal role in tumour cell adhesion to the metastatic target (86). Recently, it has been shown that Galectin-3, which is expressed in lungs (especially on the vascular endothelium), cooperates with poly-N-acetyl-lactosamine on N-glycans on B16-F1 murine melanoma cells, as a ligand for Galectin-3 (87). This interaction between Galectin-3 and its glycoprotein ligand not only facilitates initial adhesion of tumour cells to the vascular endothelium but also participates in subsequent metastatic processes such as extravasation, degradation of the matrix and organ colonization (88).…”
Section: Protumourigenic Role Of Galectin3mentioning
confidence: 99%